2017
DOI: 10.1159/000477572
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ET-1 Concentrations are Elevated in Patients with Hypertension – Meta-Analysis of Clinical Studies

Abstract: Background/Aims: A recent study revealed that global overexpression of ET-1 causes a slight reduction in systemic blood pressure. Moreover, heterozygous ET-1 knockout mice are hypertensive. The role of ET-1 in human hypertension was so far not addressed by a strict meta-analysis of published human clinical studies. Methods: We included studies published between January 1, 1990 and February 28, 2017. We included case control studies analyzing untreated essential hypertension or hypertensive patients where antih… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…In particular women with preeclampsia (hypertensive pregnant women with proteinuria) have substantially elevated plasma ET-1 concentration as compared to pregnant women with normal blood pressure. Comparing the current study results with a recent meta-analysis in non-pregnant hypertensive patients [12], it became obvious that the ET-1 elevation is much more pronounced in hypertensive pregnant women as compared to hypertensive non-pregnant patients. Our data might suggest that ET-1 play a causal role in humans in the pathogenesis of pregnancy related hypertensive diseases.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In particular women with preeclampsia (hypertensive pregnant women with proteinuria) have substantially elevated plasma ET-1 concentration as compared to pregnant women with normal blood pressure. Comparing the current study results with a recent meta-analysis in non-pregnant hypertensive patients [12], it became obvious that the ET-1 elevation is much more pronounced in hypertensive pregnant women as compared to hypertensive non-pregnant patients. Our data might suggest that ET-1 play a causal role in humans in the pathogenesis of pregnancy related hypertensive diseases.…”
Section: Discussionsupporting
confidence: 58%
“…This meta-analysis provides robust evidence that systemic ET-1 overexpression in mice lowers blood pressure in an age-dependent manner [11]. A subsequent meta-analysis -on the other hand -revealed that ET-1 plasma concentrations are elevated in humans with essential hypertension [12]. Given these contradictory findings in transgenic endothelin rodent models and humans with essential hypertension as well as the initial hypothesis that ET-1 might be involved in the pathogenesis of hypertension during pregnancy, the aim of the current study therefore was to perform a systematic review and meta-analysis of all so far published studies reporting ET-1 plasma concentrations in pregnant women.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…6 The authors reported that plasma ET-1 levels were higher by 42% in hypertensive patients than in control patients. 15 The effect of endothelin-1 on blood pressure occurs via tubular water and salt excretion, constriction of smooth muscle cells, modulating sympathetic nerve activity and vasodilatation with nitric oxide. The articles about ET-1 are about autosomal dominant PKD in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…11 Saito et al have documented the relationship between ET-1 levels and essential hypertension suggesting the causative role for ET-1 in the pathogenesis of the disease. 12,13 But the association between endothelial dysfunction, oxidation stress and systemic infl ammation in the development of pre-hypertension remains clear. Hence the present study was designed to investigate the association of endothelin-1 with oxidative stress and infl ammatory response in pre-hypertensives.…”
Section: Introductionmentioning
confidence: 99%